Three-dimensional macroassembly of chromic hydroxide - Zhou, Jiaxin; Pei, Zhenzhao (European Journal of Chemistry, 2021)
Assembly of small building blocks such as atoms, molecules, nanoparticles, and microparticles into macroscopic structures has opened up new and exciting opportunities in the realm of nanotechnology and microtechnology. Here, we report a simple hydrothermal approach for assembling chromic hydroxide microscopic particles into three-dimensional chromic hydroxide with cylindrical morphology. The morphology and size as prepared samples are controlled by the concentration of Cr(NO3)3. Our approach provides a reliable way to successfully assemble various other types of particles into cylindrical macrostructures, realizing the shape engineering of nanoscale and microscale structures to macroscopic well-defined architectures for further applications.